2017
DOI: 10.1039/c7lc00556c
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric motion of magnetically actuated artificial cilia

Abstract: Most microorganisms use hair-like cilia with asymmetric beating to perform vital bio-physical processes. In this paper, we demonstrate a novel fabrication method for creating magnetic artificial cilia capable of such a biologically inspired asymmetric beating pattern essential for inducing microfluidic transport at low Reynolds number. The cilia are fabricated using a lithographic process in conjunction with deposition of magnetic nickel-iron permalloy to create flexible filaments that can be manipulated by va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 42 publications
3
67
0
Order By: Relevance
“…Rod‐like magnetically actuated cilia have been reported to achieve spatial asymmetry, by applying an external magnetic field to rotate tilted cilia, resulting in a cone‐shaped elastic deformation path. Further, plate‐like magnetic cilia showed an enhanced planar swept area, very similar to the one observed in Paramecium, due to the interplay between stored elastic energy and the magnetic field. However, this interplay between different forces makes it difficult to precisely tune the magnitude of the various asymmetric motions separately.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Rod‐like magnetically actuated cilia have been reported to achieve spatial asymmetry, by applying an external magnetic field to rotate tilted cilia, resulting in a cone‐shaped elastic deformation path. Further, plate‐like magnetic cilia showed an enhanced planar swept area, very similar to the one observed in Paramecium, due to the interplay between stored elastic energy and the magnetic field. However, this interplay between different forces makes it difficult to precisely tune the magnitude of the various asymmetric motions separately.…”
Section: Introductionsupporting
confidence: 64%
“…However, this interplay between different forces makes it difficult to precisely tune the magnitude of the various asymmetric motions separately. Hanasoge et al showed how the swept area varies by changing the actuation frequency or the amplitude of the magnetic field, but this variation has also an impact on the orientation angle. Moreover, the phase difference between neighboring magnetic cilia is difficult to control, due to the spatial homogeneity of magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the ratio between magnetic and elastic forces acting on a cilium can be characterized by a magnetic number   is the permittivity of free space, E is the Yung's modulus, 3 12 I WP  is the bending moment of inertia, and L , W , P are the length, width, and thickness of the cilium, respectively. 25,[27][28][29] Note that in the above definition of Mn , W cancels out and, therefore, Mn is independent of cilium width. Note also that a similarly defined magnetoelastic number has been previously successfully employed in numerical simulations to describe kinematics of magnetic cilia.…”
mentioning
confidence: 99%
“…As a result, cilia perform two beating cycles for each rotation of the magnetic field. 25,27,32 The phase offset in the motion of different length cilia is illustrated in Fig. 2c.…”
mentioning
confidence: 99%
“…A ciliated cell may possess thousands of these hair-like organelles which achieve their purposes via a rhythmic whip-like beating motion, which creates fluid currents in surrounding fluid media. The emergent properties exhibited by collective ciliary motion, which are thought to be coordinated solely by local interactions [1, 2, 3, 4, 5, 6, 7, 8, 9, 10], have long-since been the focus of research for harnessing, mimicking and emulating for a range of biomedical and engineering uses [11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22].…”
mentioning
confidence: 99%